What makes a nurse today? A debate on the nursing professional identity and its need for change - van der Cingel, Margreet (Nursing philosophy, 2021)
In 2020, due to the Nightingale year and COVID-19 crisis, nursing is in the public eye more than ever. Nurses often are being seen as compassionate helpers. The public image of nursing, however, also consists of stereotypes such as nursing being a ‘doing’ profession and care being a ‘female’ characteristic. Next to that, nursing is associated with images from the past, such as ‘the lady with the lamp’. Therefore, in the public eye at least, the nursing identity seems a simple and straightforward enough construct, but nothing less is true. Looking at what a professional identity consists of, historic and social developments influence a group identity as a construct. In addition, individual, professional and contemporary societal moralities, including stereotypes, play its role. Nurses themselves reinforce stereotypes in order to fit into what is expected, even when they believe professional behaviour encompasses other features. They may do so individually as well as in a group context. But nursing actually seems to be better off when viewed upon as a diverse, autonomous profession. Moral values such as compassion motivate nurses to enter the profession. Research shows that if such values are addressed in daily practice, nursing could perhaps be saved from nurses leaving the profession because of feeling unfulfilled. Another aspect concerns the huge nursing body of knowledge. If seen as the ground on which nursing behaviour is standing, it would contribute to a different image of nursing than simplified stereotypes, which do not acknowledge the complex nature of the profession. This paper challenges the idea that the nursing identity is unchangeable and the notion that ‘a nurse will always be a nurse’. By doing so, the paper contributes to a debate on the supposed ‘true’ nature of the nursing identity and opens a discussion on the need for it to change.